Transformación digital de historias clínicas en el sector salud privado para los tipos de atención médica hospitalaria y emergencia - Olaya Espinoza, Michael Lexter (2020)
Currently, when a patient is referred to another health center, family members must carry out administrative procedures to obtain the medical history and take it to the new center where they will be cared for; this generates anguish, frustration and loss of time both for family members and especially for the patient. On the other hand, when health professionals face an emergency, they must act immediately and often without knowing the patient's entire history because they do not have such information. The opportunity is to propose a platform that allows health professionals to have information from medical records online and can review it from a portable device, without having to sit at a desktop or laptop computer to carry out this activity. For patients, give them the freedom to manage their information, so that it is displayed in the health institutions where they are attended. In this project, the use of blockchain for the management of information in medical records will be proposed through a demo developed with hyperledger composer, as well as the control of access by doctors to said information.